The white feather murders - McMillan, Rachel, 1981- (Eugene, Oregon : Harvest House Publishers, 2017)
"Toronto, 1914. Merinda Herringford and Jem Watts never could have imagined their crime-solving skills would set them up as emblems of female empowerment in a city preparing to enter World War I at the behest of Great Britain. Yet, despite their popularity, the lady detectives can't avoid the unrest infiltrating every level of society. A war measure adopted by Mayor Montague puts a target on Jem and her Italian husband. Meanwhile, deep-rooted corruption in the police force convinces their friend, Constable Jasper Forth, to quit his job and join Merinda in becoming a member of the Cartier Club--a group dedicated to weeding out the villains in local law enforcement agencies. When a club member turns up dead, bearing a slanderous white feather, will Merinda, Jem, and those they hold dear be able to solve the high-stakes mystery before they're all picked off, one by one? Join these beloved sleuths as they tackle their most treacherous case yet in the third installment of the Herringford and Watts Mysteries series"--
Keywords: Herringford, Merinda (Fictitious character) -- Fiction; Watts, Jem (Fictitious character) -- Fiction; Women detectives -- Canada -- Fiction; Murder -- Investigation -- Fiction; Historical fiction; Detective and mystery fiction; Historical mystery fiction